Lexical Coverage and Readability of Science Textbooks for English-Medium Instruction Secondary Schools in Hong Kong - Hu, Jingjing; Gao, Xuesong(Andy); Qiu, Xuyan (SAGE open, 2021)
Textbooks are an important source of knowledge input on which the transmission of academic knowledge often relies, especially in the early stages of academic learning. Adopting a corpus-based approach, this study evaluates the text difficulty of science textbooks used in secondary English-medium instruction schools in Hong Kong, with a focus on their lexical coverage and readability. It compares the English language used in English-medium science textbooks with that in English as a foreign language textbooks. The analysis reveals that the text difficulty of the English-medium science textbooks is inappropriate in terms of the coverage of academic words and the readability level. The results also show that the coverage of words from the Academic Word List (AWL) and the General Service List (GSL) as well as the text readability levels, vary across scientific topics. These findings will inform textbook design and the development of pedagogical strategies to facilitate students’ learning of subject content in the medium of English.